Activation of cannabinoid CB1 receptors suppresses the ROS-induced hypersensitivity of rat vagal lung C-fiber afferents. (October 2016) - Yeh, Chou-Ming; Ruan, Ting; Lin, Yu-Jung; Hsu, Tien-Huan
Abstract: Background: Reactive oxygen species (ROS), including H2 O2, have been shown to induce hypersensitivity of vagal lung C-fibers (VLCFs) mainly through receptor potential ankyrin 1 (TRPA1) and P2X receptors. Cannabinoids (CBs) exert antinociceptive effects by binding to specific CB receptors, designated CB1 and CB2 (type 2) for type 1 and type 2, respectively. We investigated whether activation of CB receptors can suppress ROS-mediated VLCF hypersensitivity and, if so, what type(s) of CB receptors are involved. Methods: Aerosolized H2 O2 (0.05%) was inhaled by anesthetized spontaneously breathing rats ( n = 304) to sensitize VLCFs. Airway reflex reactivity to intravenous capsaicin, a VLCF stimulant, was measured. Perivagal pretreatments with various types of agonists and antagonists, a technique that can modulate VLCF sensitivity, were made to delineate the roles of the CB receptors. Results: Aerosolized H2 O2 induced an augmented apneic response to capsaicin, which was blocked by bilateral vagotomy or by perivagal capsaicin treatment, suggesting that the response is mediated through VLCFs. Perivagal treatment with HU210 (a nonselective CB agonist) or ACPA (a selective CB1 receptor agonist), but not JWH133 (a CB2 receptor agonist), attenuated this H2 O2 -induced VLCF hypersensitivity. The suppressive effects of HU210 and ACPA were prevented by an additional treatment with AM251 (a selective CB1 antagonist), but not with AM630 (a selective CB2 antagonist). Perivagal treatment with a combination of ACPA, HC030031 (a TRPA1 receptor antagonist), and iso -PPADS (a P2X receptor antagonist) further attenuated the H2 O2 -induced VLCF hypersensitivity, as compared with treatment with a combination of HC030031 and iso-PPADS. Conclusions: Our results suggest that activation of CB1 receptors may suppress the ROS-mediated VLCF hypersensitivity through a mechanism that is at least partly distinct from the function of TRPA1 and P2X receptors. Highlights: We investigated whether activation of CB receptors can suppress the ROS-induced hypersensitivity of vagal lung C-fibers (VLCFs). Perivagal treatment with CB1, but not CB2, receptor agonist attenuated the H2 O2 -induced VLCF hypersensitivity. The mechanism underlying the attenuation of VLCF hypersensitivity by CB1 receptor activation appears to differ from the functions of TRPA1 and P2X receptors.